An appropriate inspiratory flow pattern can enhance CO2 exchange, facilitating protective ventilation of healthy lungs - Sturesson, L.W.; Malmkvist, G.; Allvin, S.; Collryd, M.; Bodelsson, M.; Jonson, B. (British journal of anaesthesia : BJA, 2016)
In acute lung injury, CO2 exchange is enhanced by prolonging the volume-weighted mean time for fresh gas to mix with resident alveolar gas, denoted mean distribution time (MDT), and by increasing the flow rate immediately before inspiratory flow interruption, end-inspiratory flow (EIF). The objective was to study these effects in human subjects without lung disease and to analyse the results with respect to lung-protective ventilation of healthy lungs. During preparation for intracranial surgery, the lungs of eight subjects were ventilated with a computer-controlled ventilator, allowing breath-by-breath modification of the inspiratory flow pattern. The durations of inspiration (TI) and postinspiratory pause (TP) were modified, as was the profile of the inspiratory flow wave (i.e. constant, increasing, or decreasing). The single-breath test for CO2 was used to quantify airway dead space (VDaw) and CO2 exchange. A long MDT and a high EIF augment CO2 elimination by reducing VDaw and promoting mixing of tidal gas with resident alveolar gas. A heat and moisture exchanger had no other effect than enlarging VDaw. A change of TI from 33 to 15% and of TP from 10 to 28%, leaving the time for expiration unchanged, would augment tidal elimination of CO2 by 14%, allowing a 10% lower tidal volume. In anaesthetized human subjects without lung disease, CO2 exchange is enhanced by a long MDT and a high EIF. A short TI and a long TP allow significant reduction of tidal volume when lung-protective ventilation is required. NCT01686984.